Evaluation of pattern and duration of university question papers in anatomy - S Viveka; M J Sudha (Wolters Kluwer Medknow Publications, 2018)
Background and objectives: Assessment drives learning. Theory summative assessment must be aligned to curricular goals. There is wide disparity in the total marks for which the examination is conducted and total duration of time of examination. The main objective of this study is to report differences in summative assessments in anatomy subject conducted by universities with respect to maximum time, maximum marks, syllabus distribution of papers, assessment of diagram drawing abilities and emphasis on clinical anatomy. Methodology: During August 2018, an extensive search for the syllabus/curriculum document will was in the internet. In the respective university websites, the document with names 'MBBS syllabus' or possible documents with syllabus details of medical undergraduate anatomy subject were searched. Results: Information from 25 different universities conducting undergraduate MBBS degree programs were evaluated. Out of these universities, sixteen universities conduct summative exam for 3 hours. Eight universities conduct exams for 2.5 hours. State universities of Punjab, Gujarat, Madhya Pradesh, Kerala and Tamil Nadu conduct anatomy exams for 50 marks with 3 hour duration. Whereas, state universities of Andhra Pradesh, Maharashtra, Assam and Odisha conduct exams for 50 marks in 2 hours. JIPMER, Pondicherry has two-hour exam for fifty marks. Only Karnataka universities [including Rajiv Gandhi University of Health Sciences and three other deemed to be universities] and All India Institute of Medical Sciences, Rishikesh conduct exams for 100 marks in 3 hours. Twenty-one universities have above diaphragm syllabus in paper 1 and below diaphragm in paper 2. Conclusion: It is the need of the hour to have a uniform, structured, objective and rationale summative assessments in anatomy